Association between Normal Thyroid Hormones and Diabetic Retinopathy in Patients with Type 2 Diabetes. (13th February 2020) - Zou, Jian; Li, Zeping; Tian, Feng; Zhang, Yi; Xu, Chao; Zhai, Jiajia; Shi, Min; Wu, Guangxian; Zhang, Zheng; Yang, Chao; Chen, Haixu; Li, Xiaomiao
Abstract : The relationship between normal thyroid function and type 2 diabetes mellitus (T2DM) has been a particular focus for concern. The present study determined the relationship between thyroid hormone levels and the prevalence of diabetic retinopathy (DR) in T2DM patients. A cross-sectional study ( n = 633) was performed in Xi'an, Shaanxi Province, China. Subjects were evaluated for anthropometric measurements, thyroid function, and diabetic retinopathy. Logistic regression models were used to assess the relationships between thyroid hormones and DR. Of 633 patients, 243 (38.4%) patients suffered from DR. The prevalence of DR showed a significantly decreasing trend across the quartiles based on free triiodothyronine (FT3) (FT3 quartile 1 group [FT3-Q1] <4.35 pmol/L, FT3 quartile 2 group [FT3-Q2] 4.35–4.70 pmol/L, FT3 quartile 3 group [FT3-Q3] 4.70–5.08 pmol/L, and FT3 quartile 4 group [FT3-Q4] ≥5.08 pmol/L) (56.7%, 42.5%, 33.1%, 23.8%, P < 0.001 ). In comparison with all participants categorized in FT3-Q1, the multivariable adjusted odds ratios (95% confidence interval) of DR in FT3-Q2, FT3-Q3, and FT3-Q4 were 0.587 (0.340–1.012), 0.458 (0.258–0.813), and 0.368 (0.201–0.673), (P = 0.055, P = 0.008, P = 0.001 ), respectively. FT3 levels within the normal range are negatively associated with DR in euthyroid patients with type 2 diabetes. Further studies should be aimed at clarifying the relationship between thyroid hormones and T2DM.